Color removal of basic and reactive dyes from simulated textile wastewater by adsorption on corn fiber and biomediated system - Valencia, Sixto A. (2000)
The use of inexpensive adsorbing material such as corn fiber and biomediated system to remove color from the simulated textile wastewater was explored. The biomediated system refers to the combined corn fiber and enriched culture of bacteria in a packed bed bioreactor. The research consists of three parts: (1) physical adsorption method using corn fiber as an adsorbent, (2) biological method using enriched culture of bacteriafor color removal, and (3) combined treatment method using corn fiber and enriched culture of bacteria. The study used four types of dyes basic blue 54 (BB54), basic red 46 (BR46), reactive blue 52 (RB52) and reactive red 120 (RR120).